2017
DOI: 10.1111/jomf.12406
|View full text |Cite
|
Sign up to set email alerts
|

Individual Wealth and Subjective Financial Well‐being in Marriage: Resource Integration or Separation?

Abstract: Economic wealth is mostly assumed to be a household‐level resource that is pooled by spouses in married couples. Using comprehensive data on the individual wealth of both spouses in married couples from the German Socio‐Economic Panel Study (N = 13,623 individuals), the author tests this assumption. To this end, the associations between individuals' wealth and their spouses' wealth with individuals' subjective financial well‐being are examined. Results show that women's financial well‐being is equally associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 26 publications
1
31
0
1
Order By: Relevance
“…The increasing labor force participation of women and their increasing economic power relative to men's has triggered a renewed interest in the study of how economic resources are managed among couples (Bennett, ; Lersch, ; Lott, ; Pepin, ). The way couples control, manage, and use their economic resources is normally studied using measures of income pooling, indicating whether the partners keep separate or joint accounts, and which spouse has the main responsibility for certain household decisions (see, e.g., Lundberg & Pollak, ; Pahl, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing labor force participation of women and their increasing economic power relative to men's has triggered a renewed interest in the study of how economic resources are managed among couples (Bennett, ; Lersch, ; Lott, ; Pepin, ). The way couples control, manage, and use their economic resources is normally studied using measures of income pooling, indicating whether the partners keep separate or joint accounts, and which spouse has the main responsibility for certain household decisions (see, e.g., Lundberg & Pollak, ; Pahl, ).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the economic and sociological literature did not find evidence of a unified model of resource pooling, whereby spouses maximize a couple‐specific utility and share resources equally among them. Such literature have instead found support for the bargaining model (i.e., for the importance of one's own rational choice rather than for a couple‐based perspective; Bennett, ; Grossbard‐Shechtman, ; Lersch, ; Lundberg & Pollak, ; Pahl, ; Pollak, ).…”
Section: Why Choose the Community Of Property At Marriage?mentioning
confidence: 99%
“…Previous research in different European contexts has generally found that, after controlling for family income, women are more satisfied financially the more income they bring to the household (Alessie, Crossley, & Hildebrand, 2006; Bonke & Browning, 2009; Newman, Delaney, & Nolan, 2008). Also, Lersch (2017) recently showed that younger generations of German women and men are more satisfied with their personal wealth than with the wealth of their partners. On the contrary, Hajdu and Hajdu (2018) revealed in the Hungarian context that neither men nor women view the higher earning potential of women positively.…”
Section: Financial Well-being and Intra-household Sharingmentioning
confidence: 99%
“…Engels (1902) highlighted the role of private property in the creation of the modern family, arguing that monogamous marriages were invented to ensure the legitimate inheritance of family wealth. Today, many scholars implicitly or explicitly assume that husbands and wives pool their resources to maximize a joint utility function promoting mutual satisfaction and wellbeing (Becker, 1981;Bennett, 2013;Lersch, 2017).…”
Section: Different Partnership Institutions Different Financial Pracmentioning
confidence: 99%